They came in the name of religion. The Islamic State in the perception of the inhabitants of Northern Iraq - Fyderek, Łukasz (Studia Etnologiczne i Antropologiczne, 2022)
This article reconstructs the perception of the Islamic State by the inhabitants of Northern Iraq, who in the years 2014–2016 lived under the rule of this quasi-state. This is a descriptive case study based on field research in Northern Iraq. It analyzes the perception of the peculiar, fundamentalist state-building process. The main findings point out that the population of Northern Iraq initially perceived IS as a legitimate organization, mostly due to their religious credentials. Over time, under the IS rule, this perception changed into a negative one. The article identifies the main challenges of the administrative apparatus and the survival strategies of the inhabitants of Northern Iraq under the rule of a fundamentalist quasi-state.